2011
DOI: 10.1530/erc-11-0076
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600E mutation, TIMP-1 upregulation, and NF-κB activation: closing the loop on the papillary thyroid cancer trilogy

Abstract: BRAFV600E is the most common mutation found in papillary thyroid carcinoma (PTC). Tissue inhibitor of metalloproteinases (TIMP-1) and nuclear factor (NF)-kB have been shown to play an important role in thyroid cancer. In particular, TIMP-1 binds its receptor CD63 on cell surface membrane and activates Akt signaling pathway, which is eventually responsible for its antiapoptotic activity. The aim of our study was to evaluate whether interplay among these three factors exists and exerts a functional role in PTCs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 52 publications
2
37
0
1
Order By: Relevance
“…A recent study of PTCs analyzed for BRAF mutation showed that BRAF V600E mutation was associated with hyperactivation of NFkB and upregulation of both TIMP1 and its receptor CD63. These studies provide insights on how BRAF V600E mutant determines cancer initiation, progression, and invasiveness in PTCs and may provide new therapeutic targets for the treatment of aggressive PTCs (Bommarito et al 2011). CD3KCD16KCD56bright immunoregulatory NK cells are increased in the tumor microenvironment and were found to be inversely correlated with advanced stages in patients with PTC (Gogali et al 2013).…”
Section: Role Of the Microenvironmentmentioning
confidence: 93%
“…A recent study of PTCs analyzed for BRAF mutation showed that BRAF V600E mutation was associated with hyperactivation of NFkB and upregulation of both TIMP1 and its receptor CD63. These studies provide insights on how BRAF V600E mutant determines cancer initiation, progression, and invasiveness in PTCs and may provide new therapeutic targets for the treatment of aggressive PTCs (Bommarito et al 2011). CD3KCD16KCD56bright immunoregulatory NK cells are increased in the tumor microenvironment and were found to be inversely correlated with advanced stages in patients with PTC (Gogali et al 2013).…”
Section: Role Of the Microenvironmentmentioning
confidence: 93%
“…The high growth rates observed in BRAF V600E tumors may be explained partially by the MAPKinduced hyperphosphorylation with consequent inhibition of the retinoblastoma (RB) protein, dependent transcription factors (E2F) and p27 of cyclin-dependent kinase (CDK) activity (36). Moreover, the BRAF oncogene induces the expression of matrix metalloproteinases (MMPs), a large group of enzymes that regulate cell-matrix composition and are important factors of tumor invasiveness (37)(38)(39). Previous studies have suggested that MMP proteins are modulated according to the intensity of MAPK pathway activation and/or signal transducer and activator of transcription (STAT) expression, which may explain the mechanism of induction of these proteins in BRAFmutated PTCs and the increased propensity of these tumors to invade surrounding tissues (37,40).…”
Section: Papillary Thyroid Carcinomamentioning
confidence: 99%
“…Inhibition reduces cell proliferation in PTC/ATC mouse tumor xenograft (6) and recently vemurafenib was shown to suppress tumor growth in BRAFV600E human ATC (7). At a molecular level, BRAFV600E mediates activation of the NF-kb transcription factor, epigenetic reprogramming through methylation, and/or expression of genes such as TIMP3, HMGB2, metalloproteases, and other structural extracellular matrix genes that can promote proliferation and cell invasion (8)(9)(10). NF-kb-driven expression of TIMP1 is also implicated in BRAFV600E thyroid cancers, able to activate the PI3K/AKT pathway sustaining cell proliferation, with one possible consequence being the over activation of the mTOR pathway (8,11).…”
Section: Introductionmentioning
confidence: 99%
“…At a molecular level, BRAFV600E mediates activation of the NF-kb transcription factor, epigenetic reprogramming through methylation, and/or expression of genes such as TIMP3, HMGB2, metalloproteases, and other structural extracellular matrix genes that can promote proliferation and cell invasion (8)(9)(10). NF-kb-driven expression of TIMP1 is also implicated in BRAFV600E thyroid cancers, able to activate the PI3K/AKT pathway sustaining cell proliferation, with one possible consequence being the over activation of the mTOR pathway (8,11). Gene expression, methylation, and molecular studies have revealed several key processes regulated by BRAF in thyroid cancer, but currently little is known about dysregulated posttranslational control of protein signaling.…”
Section: Introductionmentioning
confidence: 99%